Yo-kai watch. 6, Jibanyan evolves - Konishi, Noriyuki; Sitterson, Aubrey (VIZ Media, LLC, 2016)
Nate Adams and Whisper, his ghost-like Yo-kai friend who thinks he's Nate's butler for some reason, are at the beach when they get the urge to smash watermelons. Nate uses the Yo-kai Watch to find a Yo-kai who curses humans to want to smash watermelons, and adventure follows.